IMPROVING MATHEMATICS LEARNING OUTCOMES USING REWARD STICKERS IN ELEMENTARY SCHOOLS - Nela Rofisian; Annisa Fitri Ramadhanti; Ardita Ayu Novalia; Arif Budhiman; Arum Umul Mukaromah; Ayu Kusumayanti Pramono; Azka Syifa (El Midad, 2025)
This study aims to improve the mathematics learning outcomes of SD N 1 Wonoboyo fourth-grade students in the 2024/2025 Academic Year by implementing reward stickers. The subjects of this study were 20 fourth-grade students of SD N 1 Wonoboyo. This study used the Classroom Action Research (CAR) method with a cycle design that includes the planning, implementation, observation, and reflection stages. The data collection technique was observation and testing. The results of observations in the pre-cycle showed that only 45% of students achieved the Minimum Completion Criteria (KKM). In cycle 1, with the implementation of reward stickers, the classical completion rate increased to 65% but did not meet the target. In cycle 2, a more optimal implementation succeeded in increasing classical completion to 85%. The results of this study indicate that reward stickers can improve students' mathematics learning outcomes